2017
DOI: 10.1186/s12891-017-1588-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of frontal plane knee alignment with foot posture in patients with medial knee osteoarthritis

Abstract: BackgroundTo examine the association of radiographic frontal plane knee alignment with three-dimensional foot posture in patients with medial knee osteoarthritis (OA).MethodsParticipants in orthopedic clinics with Kellgren/Lawrence (K/L) grade ≥1 (88 patients and 88 knees; age, 61–91 years; 65.9% female) were enrolled. An anteroposterior radiographic view was used to assess the anatomical axis angle (AAA) after subtracting a sex-specific correction factor. The three-dimensional foot posture was also evaluated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 60 publications
1
50
0
Order By: Relevance
“…OA severity in the tibiofemoral joint was assessed by an experienced examiner (HI). We previously reported excellent intra-rater (k: 0.876; 95% confidence interval [CI]: 0.829 to 0.924) and inter-rater (k: 0.845; 95% CI: 0.793 to 0.897) reliability scores 14,15 . The anatomical axis angle (AAA) with sex-specific correction 16 was assessed in the anteroposterior short view in the weight-bearing position in accordance with a previously described method 14 .…”
Section: Covariatesmentioning
confidence: 99%
“…OA severity in the tibiofemoral joint was assessed by an experienced examiner (HI). We previously reported excellent intra-rater (k: 0.876; 95% confidence interval [CI]: 0.829 to 0.924) and inter-rater (k: 0.845; 95% CI: 0.793 to 0.897) reliability scores 14,15 . The anatomical axis angle (AAA) with sex-specific correction 16 was assessed in the anteroposterior short view in the weight-bearing position in accordance with a previously described method 14 .…”
Section: Covariatesmentioning
confidence: 99%
“…Lloyd & Buchanan reported that the co-contraction of the quadriceps and hamstring muscles directly supports the valgus/varus moments at the knee joint. [32] The valgus and varus moments of the knee joint can impact foot pronation and supination, respectively, [33][34][35] which may increase plantar fascia stress owing to increased pressure in the forefoot and hindfoot. [20] In the PF patients in the present study, the hamstring and quadriceps muscles showed a delayed reaction time, with greater pressure in the forefoot and hindfoot and hindfoot valgus on pedobarography, despite normal feet on plain radiographs, compared to the normal control group.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies explored whether lower extremity alignment affected HV. 2,13,14 We sought a link between asymmetric HVAs and lower extremity alignment. Iliotibial band flexibility differed significantly between the two sides.…”
Section: Discussionmentioning
confidence: 99%
“…The body forms a connected mechanical chain. 2,3,13,16 HV causes not only foot problems, but also general malalignment and muscle strength imbalance in the lower extremities. 2,3,4 The entire exercise chain requires study, i.e., not only the knee joint, but also the hip.…”
Section: Journal Of Kemamentioning
confidence: 99%